Persaingan Pengemudi Ojek Online dan Ojek Pangkalan dalam Perspektif Etika Bisnis Islam - Febi Tivani Amelia Putri; Halimah Zahrah; Mugni Nurul Ilmi; Wanda Aruniya (Teewan Journal Solutions, 2025)
This study examines the competition between online motorcycle taxis and conventional motorcycle taxi services in Indonesia, along with an evaluation from the perspective of Islamic business ethics. The research uses a qualitative literature review method, collecting data from various journals and relevant documents. Results show that competition occurs in service quality, pricing, and parking locations. Although efforts to improve service and response speed are key strategies, excessive price competition and location conflicts often lead to unhealthy rivalry. Islamic business ethics emphasize honesty, justice, prohibition of monopolistic practices, and deliberation in competition. Some drivers have applied these principles, but violations such as intimidation and price wars still occur. This study highlights the need for continuous education to internalize Islamic business ethics values, creating fair and harmonious competition.. The phenomenon of competition between online motorcycle taxis and conventional motorcycle taxi drivers in Indonesia has impacted not only the economic sector but also the social and cultural structures of society. This study aims to identify the dynamics of this competition and examine the application of Islamic business ethics principles in resolving the conflicts. Using a qualitative literature review method, data were collected from various journals, books, and official reports discussing disputes in the two-wheeled transportation sector. The findings reveal that differences in service systems, fare disparities, and competition over strategic locations are the main triggers of conflict. From the perspective of Islamic business ethics, competition should be based on fairness, honesty, deliberation (shūrā), and prohibition of harmful practices. However, these values have not been fully internalized by all drivers. This study recommends continuous education on Islamic business ethics and active involvement of government and communities in regulating operational zones and fare agreements to foster fair and ethical business competition.